Electrochemical deposition of precious metal on carbon nanotube for methanol oxidation - Saipanya S. (2014)
Precious metal nanoparticles were prepared on carbon nanotube (CNT) by sequential and simultaneous deposition methods for the electrocatalytic study of methanol oxidation. All electrochemical measurements were carried out in a three-electrode cell. A Platinum wire and Ag/AgCl were used as auxiliary and reference electrodes, respectively. Suspension of the CNT and Nafion were mixed and dropped on glassy carbon as a working electrode. Cyclic voltammograms in H 2SO 4 electrolyte solution are attributable to hydrogen adsorption and hydrogen desorption resulting in promising electrochemical performance of the prepared precious metal nanoparticles. Cyclic voltamograms of methanol electrooxidation studied in 2 M CH 3OH in 1 M H 2SO 4 show a distinguishing shape with a prominent oxidation wave in the anodic scan contributed to methanol oxidation while the cathodic scan is associated with the accumulation of carbonaceous species. © 2012 Elsevier Ltd. All rights reserved.